Supplemental Learning in Respiratory Physiology for Healthcare Professionals Towards Successful Treatment of COVID-19 - Wallace, Helen; Angus, Robert (Frontiers in Physiology, 2021)
The immunological and pathophysiological response to COVID-19 can cause severe respiratory impairment affecting gas exchange and lung mechanics. Such was the scale of the respiratory support needed during the first wave of the pandemic, that recruitment of non-respiratory clinical staff was essential to help deal with the growing number of cases. It quickly became apparent that it was vital to rapidly equip these healthcare professionals with appropriate physiological knowledge and practical skills if therapies were to be applied effectively. Furthermore, the unravelling of unusual clinical features of COVID-19, further highlighted a need for knowledge of long-established principles of respiratory physiology. An online digital educational resource, or ‘respiratory learning tool kit’ was developed with interactive material including visualisations, animations, and pathophysiological examples to facilitate understanding. The learning outcomes were centred on physiological principles, essential for understanding the pathophysiology relating to COVID-19, and management and treatment. Topics included principles of gas exchange, gas transport, homeostasis and central control of respiration. These basic physiological principles were linked to pathophysiology and clinical skills around oxygen administration and non-invasive supports such as Continuous Positive Airway Pressure (CPAP). From the degree of engagement and evaluation comments, it was clear that the resource successfully achieved its aim - to increase physiological knowledge and its practical understanding, enabling healthcare professionals to practice with confidence in such an uncertain environment.